Criticisms towards the Idea of Proper Woman in Jessie Burtons The Miniaturist - Theresia Anggarani Wardana; Ni Luh Putu Rosiandani (Universitas Sanata Dharma, 2017)
A discussion about a proper woman always includes the discussion of the concept of separate spheres. In Victorian Age for instance, a proper woman is perfectly described by the term Angel in the House. Seventeenth century Netherlands also expected the same thing for women in that era. The concept of separate spheres along with its expectations of womens proper roles is an example of social construction of gender which defines women. This study is conducted to reveal the criticisms towards the idea of proper woman in The Miniaturist.The results of this study are: first, women who are considered proper by the society in The Miniaturist have two roles, which are being a wife and being a mother. Moreover, women are also expected to have five characteristics: obedient, powerless, submissive, dependent, and domesticated. Second, The Miniaturist, using the setting in the 17th century Netherlands as a tool to criticize people in the 21st century, tries to redefine the way society thinks, including women, about womens life. The criticisms found in the novel cover four things: criticism towards womens expected roles; criticism towards womens obedience; criticism towards womens powerlessness, submissiveness, and dependence; and criticism towards womens domestication. The text tries to make women more aware of their own value. Women are also suggested to have self-dominion over themselves, and be more critical, independent, and tougher. Societys mindset regarding womens value and capability in the present time is also redefined. The most important thing is the text tries to make people in the 21st century understand women as individuals or persons who have their own right and independence.Keywords: criticism, proper woman